Radiocarbon dating and its applications in Chinese archeology: An overview - Chen, Xianglong (Frontiers in Earth Science, 2023)
Radiocarbon dating, as a well-established chronometric technique, has been widely employed in Chinese archaeology since the first radiocarbon lab started operating in the Institute of Archaeology at the Chinese Academy of Sciences in 1965. In the three decades that followed, achievements were made in radiocarbon dating studies, especially in measurement techniques, sample preparation procedures, and the establishment of regional chronological frameworks. There is no doubt that Chinese archaeology entered a golden age with the assistance of radiocarbon dating techniques at the beginning of the 2000s. It is, however, also true that compared to the western countries, China has reported far fewer radiocarbon dates than would have been desired. This paper presents an overview of the history of the radiocarbon dating technique and its significant applications in Chinese archaeology, focusing on the transition from β-decay counting to AMS. Some of the breakthroughs in the studies of the Upper Paleolithic, Early Homo sapiens, Neolithization, and the Xia and Shang dynasties were highlighted. We concluded the paper with a brief discussion of further work and research directions that are strongly desired or need to be explored.